The Pine Branch, November 1928 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1928)
The Pine Branch: Essay Issue, November 1928. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1928. Includes: editorials, photographs, poems, short stories, and other writings.
NATURE AT HER BEST | On High Top: Eunice Chute a 3 | Indian River: Lucile Nix 4 | Sunset On a Lake: Kathryn Sawyer 5 | 2 CAMPUS TALK | Thanksgiving: Mary Alexander 7 | Marks of a City: C B Sharpe 8 | On Music: Kathryn Sawyer 9 | The Charm of the Familiar: Eunice Chute 10 | 3 OLD FAMILIAR FACES | My Great Grandmother: M K Burrows 12 | Miss Pritchett Herself: Mary Alexander 13 | An Aged Friend: Dorothy Harper | Flappers and Belles: Margaret Dasher | TRIVIA FROM FOREIGN TRAVEL | The Student, As Seen By a Passenger: R Morrison Badgastein: R Morrison | Editorial : | Y W C A News | Athletic News : : | Society News | Alumnae News | Local News | Jokes
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education